SAVI Approach Paper 4: Thinking and Working Politically - Supporting partners and staff through a participatory apporach to political economy analysis - and SAVI (DFID, 2015)
Thinking and acting politically is central to the SAVI programme. We support staff and partners to analyse the power relations that shape change in their state, and to use this knowledge to inform their decision-making. This includes decisions made by SAVI state teams relating to the issues and partners they engage with and support, and...